FIRST CASE OF EXCLUSIVELY DOPAMINE-SECRETING PARAGANGLIOMA IN MULTIPLE ENDOCRINE NEOPLASIA TYPE 2A (MEN2A) - Seng, Chiew Ken; Shanty, Velaiutham; Hui, Khaw Chong (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Pheochromocytomas in MEN2A are usually intra-adrenal, though they may uncommonly manifest as paragangliomas. Predominantly or exclusively dopamine-secreting pheochromocytomas and paragangliomas (PPGL) are rare with only 33 cases reported in the literature. We report the first case of exclusively dopamine paraganglioma in the context of MEN2A. CASE A 72-year-old male was diagnosed with MEN2A following a family screening in 1996. Genetic analysis revealed a mutation in codon 634 of the RET proto-oncogene (C634Y). He underwent total thyroidectomy for medullary thyroid carcinoma in 1996 and total parathyroidectomy for primary hyperparathyroidism in 1997. His yearly 24-hour urinary catecholamines had been within the normal ranges. However, in August 2019, his urinary dopamine was raised to 1033 μg/day (Normal range: 64.0-400). Urinary adrenaline and noradrenaline were not elevated. Repeated 24-hour urinary metanephrines in August 2020 yielded an elevated 3-methoxytyramine level of 21.8 μmol/day (Normal range: 0.10-1.79). Urinary metanephrines and normetanephrines remained within normal ranges. He has hypertension which was well-controlled on two agents. He is, otherwise, asymptomatic with no paroxysmal attacks of headaches, sweating or palpitations. Iodine-131 meta-iodobenzylguanidine (I-131 MIBG) imaging revealed an avid lesion in the mediastinum with no tracer uptake at the adrenal glands. The patient declined further interventions. CONCLUSION Despite the rarity of exclusively dopamine-secreting PPGL, the case highlights the importance of measuring urinary or plasma dopamine in MEN2A. Dopamine-secreting PPGL typically lacks the classical presentation of paroxysmal attacks and is often extra-adrenal. The patient was diagnosed with PPGL at 70 years of age. As the prevalence of PPGL in MEN2A increases with age, there is no age cut-off to stop screening.